Performance of Fractional-Slot Winding PM Machines due to Un-even Coil Turns and Asymmetric Design of Stator Teeth - Mohd Luqman Mohd Jamil; Syed Muhammad S. A. Al-Habshi; Md Nazri Othman; Tole Sutikno (Institute of Advanced Engineering and Science, 2015)
PM machines in which slot number and pole number combination differs by one have to be configured with asymmetric winding pattern in order to maximize it back-emf performance. However, this asymmetric winding configuration inherently results an unwanted Unabalanced Magnetic Force (UMF). Investigations of electromagnetic performance of fractional-slot asymmetric winding PM machines using 2-D Finite-Element Analysis are presented. The investigations are mainly driven by the effort of minimizing the UMF. By employing techniques such as non-uniform number of coil turns in every tooth and asymmetric design of stator tooth, the UMF are expected can be minimized. The investigations show that the radial component of UMF has greater effect than the tangential component on the UMF itself. In all proposed techniques, a slight reduction of machine torque performance is inevitable.